2022
DOI: 10.3390/biology12010033
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Clock Explains White Matter Hyperintensity Burden Irrespective of Chronological Age

Abstract: In this manuscript we studied the relationship between WMH and biological age (B-age) in patients with acute stroke. We included in this study 247 patients with acute stroke recruited at Hospital del Mar having both epigenetic (DNA methylation) and magnetic resonance imaging data. WMH were measured using a semi-automated method. B-age was calculated using two widely used methods: the Hannum and Horvath formulas. We used multiple linear regression models to interrogate the role of B-age on WMH volume after adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Epigenetic age acceleration signi cantly contributes to explaining the volumetric burden of white matter hyperintensities, which has been found to be associated with brain aging, an increased risk of stroke, and dementia. 32,33 Several cross-sectional studies have shown a positive correlation between PhenoAge and C-reactive protein level, triglyceride levels, and waistto-hip ratio and a negative correlation with high-density lipoprotein cholesterol level. These factors have strong associations with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic age acceleration signi cantly contributes to explaining the volumetric burden of white matter hyperintensities, which has been found to be associated with brain aging, an increased risk of stroke, and dementia. 32,33 Several cross-sectional studies have shown a positive correlation between PhenoAge and C-reactive protein level, triglyceride levels, and waistto-hip ratio and a negative correlation with high-density lipoprotein cholesterol level. These factors have strong associations with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 study revealed that internalized, but not externalized, anger mediated the association between racial discrimination and JAMA Network Open | Psychiatry accelerated epigenetic aging in Black women, suggesting that this may be a viable explanation for our findings. 93 Relatedly, accelerated epigenetic aging has been associated with compromised white matter throughout the brain in different populations, 94,95 and epigenetic age acceleration has been linked to stress-related disorders and neurodegenerative disorders. [45][46][47][48]96 As such, our findings extend earlier research on accelerated aging in racially marginalized populations, showing links with brain mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This approach captures relevant differential DNAm signatures associated with a phenotype of interest. For instance, regarding cerebrovascular diseases, previous studies have demonstrated the role of DNAm in the pathogenesis of ischemic stroke, intracerebral hemorrhage, and subclinical cerebrovascular disease [ 16 , 17 , 18 ]. However, the contribution of DNAm in IA and aSAH has been less studied so far.…”
Section: Overview Of Epigenetics and Its Mechanismsmentioning
confidence: 99%